2015
DOI: 10.1039/c4cc09744k
|View full text |Cite
|
Sign up to set email alerts
|

Construction of anti-parallel G-quadruplexes through sequential templated click

Abstract: Biologically relevant DNA sequences were assembled onto addressable cyclopeptide scaffolds through sequential oxime and CuAAc reactions. The resulting conjugates are able to fold into well-defined anti-parallel DNA G-quadruplex structures, which exhibit high stability and reduced polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…KCl), before initiating the CuAAC macrocyclization reactions, was expected to drive the DNA strands of conjugate 8 to adopt an antiparallel G4 topology (as drawn in Scheme ) thereby promoting the formation of the desired product 2 . Such conformation‐assisted enhancement of the reactivity was evidenced for the assembly of 1 during which stabilizing cations were successfully used to hold the azide and alkyne groups close to each other thereby lowering the entropic cost of the reactions and preventing the formation of branched products . The stabilization of the antiparallel G4 structure of HIV‐PRO1 by K + has been reported, and we could confirm the formation, in the presence of K + , of a stable antiparallel G4 structure within 8 (vide infra, CD analysis Figure and Table ).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…KCl), before initiating the CuAAC macrocyclization reactions, was expected to drive the DNA strands of conjugate 8 to adopt an antiparallel G4 topology (as drawn in Scheme ) thereby promoting the formation of the desired product 2 . Such conformation‐assisted enhancement of the reactivity was evidenced for the assembly of 1 during which stabilizing cations were successfully used to hold the azide and alkyne groups close to each other thereby lowering the entropic cost of the reactions and preventing the formation of branched products . The stabilization of the antiparallel G4 structure of HIV‐PRO1 by K + has been reported, and we could confirm the formation, in the presence of K + , of a stable antiparallel G4 structure within 8 (vide infra, CD analysis Figure and Table ).…”
Section: Resultssupporting
confidence: 61%
“…The conversion of conjugate 8 to conjugate 2 was then performed under nonstandard CuAAC conditions previously developed for the synthesis of conjugate 1 . The intramolecular reactions were performed in 4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer (pH 7.4) and in the presence of copper sulfate (CuSO 4 ), tris(benzyltriazolylmethyl)amine (THPTA) ligand, sodium ascorbate, and 100 m m potassium chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is also relevant in the present case, as it does not rely on the luminescence of the complexes. We used a recently reported method based on a template‐assembled synthetic G‐quadruplex (TASQ) strategy that allows the formation of highly stable G‐quadruplex structures with precise control of G‐quadruplex topology through the assembly of constrained structures on a template (Figure ) . This method has been successfully used to probe the interaction modes of several G4‐binding ligands .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, we and others have demonstrated that the thermodynamic stability of distinct G4 folds could be increased by site‐specifically fixing DNA‐G4‐forming sequences onto rigid molecular scaffolds. By using regioselectively addressable cyclopeptide platforms, a full parallel tetrameric (Figure B) along with an antiparallel dimeric DNA‐G4 topology were assembled . As expected, the resulting folded topologies displayed high stability and reduced polymorphism and could find applications in the exhaustive evaluation of ligand binding properties .…”
Section: Introductionmentioning
confidence: 99%